Purchase Intention Kosmetik Lokal Berbasis Budaya: Peran Brand Awareness dan Trust pada Generasi Z - Indri Ferdiani Suarna (Journal of Innovative and Creativity, 2025)
The significant development of the cosmetics sector in Indonesia reflects a growing public awareness particularly among Generation Z regarding the importance of personal care. Sariayu Martha Tilaar, as a local brand that promotes cultural values, faces considerable challenges in maintaining its relevance amidst the dominance of modern and global brands. This study focuses on investigating the extent to which brand awareness and consumer trust influence the purchase intention of Sariayu Martha Tilaar products among Generation Z consumers in Bandung. A quantitative approach was adopted, employing a survey method to collect primary data from 400 respondents selected through purposive sampling, ensuring that only individuals meeting the target criteria were involved. To analyze the relationship among the research variables, multiple linear regression was applied using SPSS version 25. The statistical results indicate that both brand awareness and trust have a positive and significant effect on purchase intention, both individually and simultaneously. Trust was found to have the most dominant influence, with a beta coefficient of 0.568 and a significance level of < 0.001. The coefficient of determination (R²) at 0.620 indicates that 62% of the variance in purchase intention can be explained by these two variables. These findings highlight the crucial role of strengthening brand trust and awareness strategies in enhancing the purchase intention of young consumers toward local, culture-based cosmetic products.